2004
DOI: 10.1039/b402722a
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure determination and calcium binding effects of lipopeptide antibiotic daptomycin

Abstract: Daptomycin is an acidic lipopeptide antibiotic, whose three-dimensional structure and mechanism of action is currently unknown. Recently daptomycin, trade name Cubicin, was approved as a drug for the treatment of skin-related infections (M. Larkin Lancet, 2003, 3, 677) and became the first antibiotic of its class to be used in the clinic (A. Raja et al., Nature Rev. Drug Discov., 2003, 2, 943-944). We have carried out a systematic high field NMR study of daptomycin and its binding to calcium ions which is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 23 publications
7
98
1
Order By: Relevance
“…42 Ball et al also reported the structure of Ca 2+ -bound daptomycin using an 0.8 mM solution of daptomycin at pH 5.3. 36 There were no major differences between their Ca 2+ -daptomycin structure and their apo-daptomycin structure.…”
Section: Solution Structure Of Calcium-bound Daptomycinmentioning
confidence: 89%
See 4 more Smart Citations
“…42 Ball et al also reported the structure of Ca 2+ -bound daptomycin using an 0.8 mM solution of daptomycin at pH 5.3. 36 There were no major differences between their Ca 2+ -daptomycin structure and their apo-daptomycin structure.…”
Section: Solution Structure Of Calcium-bound Daptomycinmentioning
confidence: 89%
“…Line broadening increased up to 1 equivalent of Ca 2+ and then ceased. 36 The change in line width had a sigmoidal dependence on the amount of Ca 2+ added, suggesting cooperative binding. The addition of Ca 2+ did not result in discernible changes to chemical shifts.…”
Section: Calcium-induced Aggregation and Its Role In Daptomycin Delivmentioning
confidence: 92%
See 3 more Smart Citations